Junior high school student perception of online learning in pandemic Covid-19: Gender, social media ownership, and internet access duration perspective - Muhammad Ramdhan; Moh. Irma Sukarelawan; M. Anas Thohir; Fitria Arifiyanti (Association for Scientific Computing Electrical and Engineering(ASCEE), 2022)
This study aims to explore students’ perceptions of the implementation of online learning during the pandemic in terms of gender perspective, ownership of social media, and duration of internet access. This research was conducted by a survey involving 87 students (P = 51% and L = 49%) in junior high school. Data were analyzed using Logit Value of Item (LVI) and Wright map combined with Logit Value of Person (LVP). Students’ perceptions were reviewed based on gender, social media ownership, and duration of daily internet access. The results showed that, in general, students have a positive perception of online learning. Based on gender, male and female students have almost the same positive perception of online learning. In terms of ownership of social media accounts, students with one account or two social media accounts have a perception of online learning above the average logit person. Most students who access the internet for more than 5 hours have a perception above the average logit person. Students whose internet access duration is 3-4 hours have a perception above the average logit person. So, gender, social media ownership, and internet access duration of 3-4 hours have positive perceptions of online learning.